The kids market - Beyrouti, Nouri (2013)
In the world of marketing and advertising, children are the target. For many reasons children are exerting a greater influence on family buying decisions. Marketers and advertisers know that the money is in the hands of children. Children's influence in family purchase decisions was found to vary by product category and brand choice decision-related factors, as well as by demographic and lifestyle factors, and family household structure. As their economic muscle grows, so does a marketer's focus. Understanding how and why a child influences purchasing decisions is important to marketers and strategic marketing planning. Hence, it seems that if researchers wish to fully understand family decision making, children should be included in studies of family consumer behavior. The purpose of this paper is to examine the roles and tactics that children have in affecting family buying decision making. And to evaluate the influence of Lebanese kids on their families' buying behavior and buying patterns.